2019
DOI: 10.1186/s12885-019-6009-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and cancer in adolescents and young adults - a comparison between reproductive cancer patients and patients with non-reproductive cancer

Abstract: Background Sexuality is an important aspect of quality of life for adolescent and young adults that remains understudied in cancer patients. Most current knowledge about how cancer and cancer treatments can affect patients’ sexuality pertains to reproductive cancer patients (breast, gynecological, male reproductive organs), whereas only little is known about how the disease affects the sex lives of patients with other types of cancer. This study examined sexual satisfaction and sexual supportive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 68 publications
3
48
2
Order By: Relevance
“…According to their results, sexuality is significantly worse in women with tumours affecting the reproductive sphere. More specifically, the Authors reported a significant deterioration of sexual satisfaction, changes in sexuality and increased sexual supportive care needs [39]. Similar data were highlighted in the study by Geue et al [40], which investigated couple relationships and sexuality in adolescents and young adults with cancer.…”
Section: The Impact Of Cancer and Fertility Preservation On Quality Osupporting
confidence: 64%
See 1 more Smart Citation
“…According to their results, sexuality is significantly worse in women with tumours affecting the reproductive sphere. More specifically, the Authors reported a significant deterioration of sexual satisfaction, changes in sexuality and increased sexual supportive care needs [39]. Similar data were highlighted in the study by Geue et al [40], which investigated couple relationships and sexuality in adolescents and young adults with cancer.…”
Section: The Impact Of Cancer and Fertility Preservation On Quality Osupporting
confidence: 64%
“…Several studies have investigated the impact of reproductive cancers on sexual satisfaction and needs of women of reproductive age. Mütsch et al [39] investigated sexual function and the needs related to the sexual sphere of adolescents and young women affected by both reproductive and other types of cancer. According to their results, sexuality is significantly worse in women with tumours affecting the reproductive sphere.…”
Section: The Impact Of Cancer and Fertility Preservation On Quality Omentioning
confidence: 99%
“…Sexual desire and sexual behaviours/activities, two of the main components of sexuality, have been widely studied and proven to be associated with other diseases such as cardio‐cerebrovascular diseases, psychological and psychiatric diseases, chronic metabolic diseases and several kinds of malignant tumours, as well as with the male death rate generally (Brody & Preut, 2003; Costa & Brody, 2012; Ebrahim et al, 2002; Fischer, Marguerie, & Brotto, 2019; Holloway & Wylie, 2015; Lee, Nazroo, O’Connor, Blake, & Pendleton, 2016; Mütsch et al, 2019; Palmore, 1982; Rider et al, 2016; Smith, Frankel, & Yarnell, 1997; White et al, 2012; Yang, Lu, Song, Chen, & Liu, 2019; Yang, Song, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that over 40% of young adults with cancer experience sexual problems within the first 2 years following diagnosis [ 4 , 5 ]. Problems commonly reported by women include reduced sexual desire, vaginal dryness and/or dyspareunia, difficulties in sexual arousal and/or orgasm, and low satisfaction with sex life [ 6 8 ]. In men diagnosed with cancer erectile dysfunction, orgasmic difficulties, reduced sexual interest, and low satisfaction with sex life have been reported [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%